Genetic-molecular characterization in the diagnosis of primary immunodeficiencies (2020)
Objectives: To rescue medical genetics concepts that are necessary to understand the advances in the genetic-molecular characterization of primary immunodeficiencies, to help in the understanding and adequate interpretation of their results. Source of Data: Non-systematic literature review, searching for articles since 2000 on PubMed using the terms ‘‘genetic evaluation’’ OR ‘‘whole exome sequence’’ or ‘‘whole genome sequence’’ OR ‘‘next generation sequence’’ AND ‘‘immunologic deficiency syndromes’’ OR ‘‘Immune deficiency disease’’ OR ‘‘immune deficiency’’ NOT HIV. Summary of the data: Knowledge of medical genetics is essential for the understanding of the principles of heredity and disease inheritance patterns, types of genetic variants, types of genetic sequencing and interpretation of their results. The clinical and immunophenotypic evaluation of each patient is essential for the correlation with the genetic variants observed in the genetic study of patients with primary immunodeficiencies. The discussion of the benefits and limitations of genetic tests should always guide the performance of genetic tests. Conclusions: There are many evident benefits of genetic analysis, such as the definitive diagnosis of the disease, family genetic counseling, and the possibility of a more adequate and accurate management. Cost, access and interpretation of genetic test results are limitations that need continuous improvement. The understanding of the benefits and limits of the several genetic assessment methodologies related to primary immunodeficiencies is essential to obtain more effective results from the sequencing.